The Vākyārthamātṛkā of Śālikānatha Miśra with his own vṛtti - Śālikanāthamiśra (Sri Garib Das oriental series, 1987)
Verse work, with autocommentary, on semantics according to the Mīmāṃsā school in Indic philosophy.